Burkina Faso : Fourth and Fifth Reviews Under the Extended Credit Facility Arrangement, Request for a Waiver of Nonobservance of Performance Criterion and Rephasing of Access-Press Release; Staff Report; and Statement by the Executive Director for Burkina Faso. (IMF Staff Country Reports; Country Report ;, 2020)
The security crisis is worsening and is leading to disruption of basic public services and an unprecedented humanitarian crisis. The Covid19 outbreak and the authority's response to contain its spread further compounded the situation. Presidential and legislative elections are scheduled for November 2020. Outlook and risks. The economic impacts of the global and domestic measures to contain the spread of the COVID19 pandemic have been stronger than expected. Real GDP contracted by 1.4 percent and 8.6 percent (y-o-y) in the first and second quarters of 2020, respectively. The economic outlook remains uncertain, with growth expected to stand around -2.8 percent in 2020 (down from 6 percent forecast prior to the pandemic). Inflation is expected to pick up and reach 4.1 percent by end-2020. The fiscal deficit in 2020 is expected to widen to about 5.3 percent of GDP, to accommodate an effective response to the Covid19 and security shocks. The main risks to the outlook are the uncertainty surrounding the duration of the pandemic and the security crisis.